Cerium oxide nanoparticles: properties, biosynthesis and biomedical application. Issue 45 (21st July 2020) - Singh, Kshitij RB; Nayak, Vanya; Sarkar, Tanushri; Singh, Ravindra Pratap
Abstract : Cerium oxide nanoparticles have revolutionized the biomedical field and is still in very fast pace of development. Hence, this work elaborates the physicochemical properties, biosynthesis, and biomedical applications of cerium oxide nanoparticles. Abstract : Nanotechnology is the branch of science which deals with particles ranging between 1–100 nm. These particles are called nanoparticles, and they exhibit unique electronic, optical, magnetic, and mechanical properties, which make them different from the bulk material. These properties of nanomaterials help them to find a variety of applications in the biomedical, agricultural, and environmental domains. Cerium oxide nanoparticles have gained a lot of attention as a potential future candidate for ending various kinds of problems by exhibiting redox activity, free radical scavenging property, biofilm inhibition, etc. Synthesis of these nanoparticles can be performed very easily by utilizing chemical or biological methods. But in this review, the focus is laid on the biosynthesis of these nanoparticles; as the biosynthesis method makes the cerium oxide nanoparticle less toxic and compatible with the living tissues, which helps them to find their path as an anticancer, anti-inflammatory and antibacterial agents. The pre-existing reviews have only focused on details relating to properties/applications/synthesis; whereas this review draws attention towards all the aspects in single review covering all the details in depth such as biosynthesis methods and its effect on the living tissues, along with properties, biomedical applications (diagnostic and therapeutic) and future outlook of the cerium oxide nanoparticle.